The direct anterior approach in total hip arthroplasty: a systematic review of the literature. (June 2017) - Meermans, G.; Konan, S.; Das, R.; Volpin, A.; Haddad, F. S.
Abstract : Aims: The most effective surgical approach for total hip arthroplasty (THA) remains controversial. The direct anterior approach may be associated with a reduced risk of dislocation, faster recovery, reduced pain and fewer surgical complications. This systematic review aims to evaluate the current evidence for the use of this approach in THA. Materials and Methods: Following the Cochrane collaboration, an extensive literature search of PubMed, Medline, Embase and OvidSP was conducted. Randomised controlled trials, comparative studies, and cohort studies were included. Outcomes included the length of the incision, blood loss, operating time, length of stay, complications, and gait analysis. Results: A total of 42 studies met the inclusion criteria. Most were of medium to low quality. There was no difference between the direct anterior, anterolateral or posterior approaches with regards to length of stay and gait analysis. Papers comparing the length of the incision found similar lengths compared with the lateral approach, and conflicting results when comparing the direct anterior and posterior approaches. Most studies found the mean operating time to be significantly longer when the direct anterior approach was used, with a steep learning curve reported by many. Many authors used validated scores including the Harris hip score, and the Western Ontario and McMaster Universities Arthritis Index. These mean scores were better following the use of the direct anterior approach for the first six weeks post-operatively. Subsequently there was no difference between these scores and those for the posterior approach. Conclusion: There is little evidence for improved kinematics or better long-term outcomes following the use of the direct anterior approach for THA. There is a steep learning curve with similar rates of complications, length of stay and outcomes. Well-designed, multi-centre, prospective randomised controlled trials are required to provide evidence as to whether the direct anterior approach is better than the lateral or posterior approaches when undertaking THA. Cite this article: Bone JointJ 2017;99-B:732–40.